2017
DOI: 10.1007/s10517-017-3640-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfation and Molecular Weight on Anticoagulant Activity of Dextran

Abstract: Sulfation (to 2.8) of dextrans with molecular weight of 150 and 20 kDa was followed by the appearance of anticoagulant activity that increased with decreasing their molecular weight and did not depend on antithrombin, plasma inhibitor of serine proteases of the blood coagulation system. Antithrombin activity of dextran sulfate with a molecular weight of 20 kDa reached 12.6-15.3 U/mg. Dextran sulfates with molecular weights of 20 and 150 kDa did not potentiate ADP-induced human platelet aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…As we know, effects of HBOCs on platelet aggregation or coagulation relates with the safety. However, Toussaint et al proposed that hemoglobin conjugated to macromolecules of dextran benzene tetracarboxylate did not alter platelet aggregation in vitro using flow cytometry [18] and Drozd et al [19] found that Dextran sulphates with molecular weights of 20 and 150 kDa did not potentiate ADP-induced human platelet aggregation. Referring to these articles, we suggest that Dex-bHb was counted as little impact on platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, effects of HBOCs on platelet aggregation or coagulation relates with the safety. However, Toussaint et al proposed that hemoglobin conjugated to macromolecules of dextran benzene tetracarboxylate did not alter platelet aggregation in vitro using flow cytometry [18] and Drozd et al [19] found that Dextran sulphates with molecular weights of 20 and 150 kDa did not potentiate ADP-induced human platelet aggregation. Referring to these articles, we suggest that Dex-bHb was counted as little impact on platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the graph of the dependence of the plasma coagulation time on the concentration of NMIC derivatives, concentrations of 2APTT (mg/mL) were determined at which the plasma coagulation time was twice as long as in the control with the addition of 0.05 M Tris-HCl buffer (with 0.175 M NaCl, pH 7.4) instead of sample. When calculating the antithrombin activity (aIIa), NMIC derivatives calibrated the test system for unfractionated heparin (HEPARIN-BELMED, 25,000 units) (RUP Belmedpreparations, Minsk, Belarus) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dextran sulfate (DexS) is another heavily sulfated semisynthetic polysaccharide that exhibits non-serpin mediated anticoagulant activity (Drozd et al, 2017). Like heparin it can be quantified by its interaction with protamine (Gordon et al, 2021), and it is cleared from the circulation by the HARE scavenger of endothelial cells (Weigel, 2020).…”
Section: G Chemically Sulfated Polysaccharidesmentioning
confidence: 99%